Basal Cell Carcinoma After High Dose Rate Brachytherapy: Medium-term Dermoscopic Evaluation of Cancer’s Response - Tomasz Krzysztofiak; Magdalena Suchorzepka; Andrzej Tukiendorf; Piotr Wojcieszek; Grażyna Kamińska-Winciorek (Dermatology and Therapy, 2023)
Abstract Introduction Basal cell carcinoma of the facial region remains a challenge for contemporary oncology due to the presence of aesthetic regions and critical organs. Surgery is not always the optimal solution, and high dose rate (HDR) brachytherapy has emerged as an organ-sparing treatment method whose effectiveness has been proven by a growing number of publications. Dermoscopy is a diagnostic tool that bridges clinical and pathological examination of skin lesions. It is routinely used for diagnosis, monitoring of treatment, and post-treatment evaluation; however, the literature lacks data concerning changes in dermoscopic patterns of skin cancers during and after irradiation. Methods Our team conducted a prospective non-randomized trial of 39 patients with high-risk basal cell carcinomas (BCCs), mostly localized within the high-risk zone (H-zone) of the facial region, and who qualified for HDR brachytherapy. HDR contact brachytherapy with custom-made surface molds was introduced, delivering a dose of 45 Gy in 9 fractions prescribed to the tumor. Every patient was observed clinically and dermoscopically at three observational points: before treatment, at the end of treatment (3rd week), and 24 weeks after the end of therapy. The evolution of clinical and dermoscopic patterns was observed by two independent dermoscopists using current diagnostic criteria. A database of 12,088 photographic observations was evaluated. Results Univariate logistic regression proved that brachytherapy decreases the number of clinical and dermoscopic patterns typical for basal cell carcinoma, as well as dermoscopic features not related to BCC, presumably due to the formation of scar tissue. In addition, univariate logistic regression with random effects proved a positive correlation between tumor size and presence of various dermoscopic patterns typical for BCC. Conclusion Dermoscopy is proven to be easy to perform and an adequate monitoring tool for patients with BCCs undergoing HDR brachytherapy.